The inhibitory mechanism of humic acids on photocatalytic generation of reactive oxygen species by TiO2 depends on the crystalline phase - Lee, Youn Jun; Jae Jeong, Yoo; Sun Cho, In; Lee, Chang Gu; Park, Seong Jik; Alvarez, Pedro J.J. (Chemical Engineering Journal, 2023)
To enable the practical use of TiO2 for photocatalytic water treatment, it is important to understand how dissolved natural organic matter affects its photocatalytic activity and the mechanisms involved in generating reactive oxygen species (ROS). In this study, we systematically investigated the inhibitory effects of humic acids (HA) on 4-chlorophenol (4-CP) degradation using two common TiO2 crystalline phases (anatase and rutile) individually. HA strongly hindered the photocatalytic activity of anatase, with an Ra (the ratio of the first-order rate constant for 4-CP degradation in the absence vs. presence of 30 mg/L HA) of 2.30 (±0.13). This ratio was significantly higher than that of rutile (Rr = 1.21 ± 0.08), which was less susceptible to this inhibitory effect and even exhibited improved photocatalytic activity at HA concentrations below 20 mg/L. Similar trends were observed for various HA sources, corroborating the crystalline-phase-dependent effect of HA. Adsorption experiments, Fourier transform infrared spectroscopy, and photoelectrochemical analyses suggested that the adsorption mechanisms and hole-scavenging effect of HA on the two TiO2 polymorphs did not differ. Importantly, scavenger, probe, and electron spin resonance experiments revealed that the difference in inhibitory effects of HA originate from the distinct ROS generation mechanisms for the two polymorphs. The oxygen reduction pathway for [rad]OH generation over anatase was hindered by surface-adsorbed HA, while the water oxidation pathway for [rad]OH generation over rutile was less affected. Furthermore, surface-adsorbed HA boosted O2[rad]− generation on rutile, increasing 4-CP degradation efficiency. This mechanistic insight into NOM-TiO2 interactions informs materials selection and strategies for higher TiO2 photocatalytic performance in different water matrices.
Keywords: 4-chlorophenols; Crystalline phasis; Humic acid; Inhibitory effect; Inhibitory mechanism; Natural organic matters; Photo-catalytic; Photocatalytic activities; Photocatalytic oxidations; Reactive oxygen species; Crystalline phase; Humic acids; Natural organic matter; Photocatalytic oxidation; Reactive oxygen species; TiO2